2013
DOI: 10.1007/s10973-013-3586-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal decomposition of ammonium metatungstate

Abstract: The structure, morphology of ammonium metatungstate (AMT), (NH 4 formed between 380-500 °C, (iv) which then transformed into the more stable m-WO 3 between 500-600 °C. As a difference in air, the as-formed NH 3 ignited with an exothermic heat effect, and nitrous oxides formed as combustion products. The thermal behavior of AMT was similar to ammonium paratungstate (APT), (NH 4 ) 10 [H 2 W 12 O 42 ]•4H 2 O, the only main difference being the lack of dry NH 3 evolution between 170-240 °C in the case of AMT.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 53 publications
(51 reference statements)
8
54
0
Order By: Relevance
“…Several scientific papers have reported the thermal behavior of tungsten-related material [2][3][4][5][6][7][8][9][10]. For example, Hunyadi et al [6] reported the thermal behavior of "ammonium metatungstate", and Van put [10] reported "ammonium paratungstate."…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific papers have reported the thermal behavior of tungsten-related material [2][3][4][5][6][7][8][9][10]. For example, Hunyadi et al [6] reported the thermal behavior of "ammonium metatungstate", and Van put [10] reported "ammonium paratungstate."…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hunyadi et al [6] reported the thermal behavior of "ammonium metatungstate", and Van put [10] reported "ammonium paratungstate." Although current papers describe well information about experimental results and analysis, fundamental reason behind the change of physicochemical properties (including size, crystallinity, and physical properties) during the thermal decomposition process is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes are accompanied by endothermic effects. Mass loss recorded in this stage of decomposition of WP (5.0 mass %) is considerably greater than the mass loss (2.4 mass %) recorded in analogous stage of decomposition by Hunyadi et al [10]. The third stage of investigated process commences at 220°C, runs with 4.5 % mass loss and is also accompanied by endothermic effect.…”
Section: Resultsmentioning
confidence: 49%
“…Hunyadi and coworkers [10] In order to know WO 3 content in WP, sample of tungsten precursor was subjected to DTA-TG investigations. Figure 2 shows DTA and TG curves of WP.…”
Section: Resultsmentioning
confidence: 99%